Allergen immunotherapy for asthma prevention: A systematic review and meta-analysis of randomized and non-randomized controlled studies - Farraia, M (2022)
Background: Allergen immunotherapy (AIT) is a disease-modifying treatment for IgE-mediated diseases. Randomized controlled trials (RCTs) support AIT's potential role in asthma prevention but evidence from non-randomized studies of interventions (NRSI) and longitudinal observational studies has been poorly addressed. Therefore, we aimed to conduct a systematic review and meta-analysis to assess clinical data from all study types to evaluate quantitatively the preventive role of AIT in asthma onset. Methods: We search three databases. Studies were screened, selected and evaluated for quality using risk-of-bias (ROB) tools. Data were descriptively summarized and meta-analysed using random effects. We performed a sensitivity, influence and subgroup analyses. Publication bias and heterogeneity were assessed. Results: From the 4549 identified studies, 24 (12 RCTs and 12 NRSI) were included in the qualitative synthesis and 18 underwent meta-analysis. One study was at low ROB, seven had moderate ROB, and 15 were proven of high ROB. Random-effects analysis showed a significant decrease in the risk of developing asthma following AIT by 25% (RR, 95% CI: 0.75, 0.64–0.88). This effect was not significant in the sensitivity analysis. Publication bias raised concerns, together with the moderate heterogeneity between studies (I2 = 58%). Subgroup analysis showed a remarkable preventive effect of AIT in children (RR, 95% CI: 0.71, 0.53–0.96), when completing 3 years of therapy (RR, 95% CI: 0.64, 0.47–0.88), and in mono-sensitized patients (RR, 95% CI: 0.49, 0.39–0.61). Conclusions: Our findings support a possible preventive effect of AIT in asthma onset and suggest an enhanced effect when administered in children, mono-sensitized, and for at least 3 years, independently of allergen type. © 2022 European Academy of Allergy and Clinical Immunology and John Wiley & Sons Ltd.